Production of hydrogen from hydrogen sulfide with perovskite type catalysts: LaMO3 - Guldal, N. O.; Figen, H. E.; Baykara, S. Z. (ELSEVIER SCIENCE SA, 2017)
Catalytic thermal decomposition of 1% (vol.) hydrogen sulfide (H2S) was studied by using perovskite type catalysts within a temperature range between 600 degrees C and 950 degrees C and at atmospheric pressure in a quartz tubular reactor, with the aim of producing hydrogen. Lanthanum was selected as an A-site element from the lanthanide series and M: Ce, Co, Cr, Cu, Mo, Sr, V were selected for the B-site in order to build up the perovskite structure as La(M)O-3. The influence of different transition metals (Co, Cr, Cu, Mo, V) as well as of alkaline earth (Sr) and of lanthanide (Ce) doping on both catalyst structure and catalytic activity was investigated through catalyst characterization and catalyst activity tests. Structural characterizations of fresh and spent catalysts were performed by XRD and SEM-EDS methods. The most active catalyst was found to be LaCrO3 at 750 degrees C with a conversion value of 14%, the highest among the seven catalysts at that temperature. Moreover, conversion values such as 5%, and 22% that were achieved at similar to 650 degrees C and similar to 825 degrees C using LaCrO3, were only possible at higher temperatures, 900 degrees C and 950 degrees C via direct thermal decomposition. La2SrOx. fresh sample, had the largest specific surface area, 10.05 m(2)ig, among the seven catalysts studied, and it gave the highest conversion of 35.7% at 950 degrees C. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Hydrogen production; Hydrogen sulfide; Catalyst; Perovskite; THERMAL-DECOMPOSITION; THERMOCHEMICAL DECOMPOSITION; METHANE COMBUSTION; CLAUS PROCESS; H2S; SULFUR; VANADIUM; THERMOLYSIS; SEPARATION; PYROLYSIS; Engineering